What do patients expect from their physicians? Qualitative research on the ethical aspects of patient statements - (:unkn) unknown (BMJ PUBLISHING GROUP, 2012)
This study aimed to examine the thoughts and expectations of patients receiving healthcare from their physicians and evaluate the ethical aspects of these thoughts and expectations. To determine the ethical aspects of the thoughts and expectations of patients, an open-ended question was asked on the web page of the Turkish Armed Forces (TAF) Health Care Command, which is accessible to the users of the TAF intranet system (the internet system used within TAF institutions). The participants were asked to express their thoughts in their own words. A total of 804 participants answered the question by providing their input. The statements of the participants were classified separately by two public health specialists. The classification was made in accordance with the basic principles of patient rights, and they were collected under various headings including expectations about respect and care, good communication, informed consent, and fair and non-privileged distribution of healthcare services. The results show that patients tend to consider the physicians they see as solely responsible for all the negative issues that they encounter during their healthcare. This indicates that there is a need for extensive research on the underlying factors involved in the negative thoughts and feelings toward healthcare professionals in both TAF and Turkey in general.
Keywords: AGREEMENT